A combined modality of carboplatin and photodynamic therapy suppresses epithelial-mesenchymal transition and matrix metalloproteinase-2 (MMP-2)/MMP-9 expression in HEp-2 human laryngeal cancer cells via ROS-mediated inhibition of MEK/ERK signalling pathway. Issue 8 (November 2016) - Mao, Wenjing; Sun, Yan; Zhang, Huankang; Cao, Luhong; Wang, Jiajia; He, Peijie
Abstract Photodynamic therapy (PDT) has been developed as a promising treatment modality for laryngeal cancer. 9-Hydroxypheophorbide α (9-HPbD), a novel chlorophyll-derived photosensitizer, has a longer absorption wavelength, which increases the penetration of light to malignant tissues. Carboplatin (CBDCA), a second-generation platinum derivative, also has gained more popularity for the treatment of laryngeal cancer. Our previous studies have elucidated that 9-HPbD-PDT could inhibit the migration and invasion of HEp-2 cells. The objective of this study is to investigate the change of migration and invasion of HEp-2 cells induced by a combined modality of CBDCA and 9-HPbD-PDT in vitro. A wound healing assay, cell migration assay and Matrigel invasion assay were used to evaluate the cellular migration and invasion. Reactive oxygen species (ROS) and Western blots for epithelial-mesenchymal transition (EMT) markers (E-cadherin, N-cadherin and vimentin), MMPs (MMP-2 and MMP-9) and MEK/ERK signalling pathway were performed to investigate the possible mechanisms that may be involved. We observed that CBDCA and 9-HPbD-PDT administration synergistically inhibited the migration and invasion of HEp-2 cells. Moreover, the combined modality cooperatively repressed the EMT process and down-regulated expressions of MMP-2 and MMP-9 via ROS-mediated inhibition of phosphorylation in the MEK/ERK signalling pathway. Our results suggested that the combination of CBDCA and 9-HPbD-PDT might be a promising therapeutic strategy for laryngeal cancer metastasis.